Головна редколегія науково-документальної серії книг “Реабілітовані історією” інформує.... (З архівів ВУЧК-ГПУ-НКВД-КГБ, 2004)
The part “Chronicle and information” contains proceedings and decrees of main editorial board of research team of the series of book “Rehabilitated by history” for 2004.